Effect of pyrolisis temperature and number of molasses’s adhesive toward quality of mud cake based bio briquette - Andy Candra (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Biomass waste utilization can be one solution to find another alternative fuels that can be renewable. Two kinds of biomass which were used in this research are mud cake (produce from rotary vacuum filter in sugar production process) which was used as the raw material and molasses which was used as an adhesive. First, the mud cake was dried and pyrolyzed became charcoal. Then, the charcoal mixed with water and molasses, formed into a cylindrical shape, and dried it up to be a combustible bio briquettes. The quality of bio briquette was dependent on kind of raw materials, quantity of adhesive, temperature of pyrolysis, and compaction pressure. The result: the lower pyrolysis temperature, the more yield of charcoal, but it followed by the shorter flaming time, the shorter combustion time, and lower calorific value. Besides, the more molasses use, the bio briquette become more compact and more flammable but it had shorter combustion time. Pyrolysis temperature influences the compressive strength, besides, amount of adhesive influences the flaming time and combustion time. Overall, the best bio briquette can be produced with conditions of pyrolysis temperature 600 °C and ratio between molasses and charcoal 0.3.